Zoonoses and Animal Culling: The Need for One Health Policy. Issue 5 (13th October 2022) - Lederman, Zohar
Abstract: One Health (OH) as a biomedical and social movement calls to reorient public health approaches toward more holistic, nonanthropocentric approaches that do not exclude the interests of animals and ecosystems. OH thus urges reexamination, from both scientific and moral perspectives, of the practice of culling pet, farm, or wild animals in the face of a zoonosis. Pandemics such as Covid and monkeypox highlight the need for more rigorous analysis of the justifications traditionally provided to back these culling practices. Such analyses should then ground reasonable OH policies and legislation that consider the rights of humans, animals, and the environment. Bill S.861, "Advancing Emergency Preparedness through One Health Act of 2021, " which was introduced in the U.S. Congress, is a step in the right direction .